2020
DOI: 10.1177/0030727020948967
|View full text |Cite
|
Sign up to set email alerts
|

Confronting genetic gains with markets: Retrospective lessons from New Rice for Africa (NERICA) in Uganda

Abstract: Breeders have two non-exclusive strategic investment options for increasing smallholder farmers’ and consumers’ livelihoods through genetic improvement of crop varieties: (i) enhancing productivity; and (ii) enhancing value and market access. New Rice for Africa (NERICA) varieties with superior agronomic characteristics were bred and introduced in various African countries in the early 2000s. Two decades later, drought tolerant NERICA4 is among the popular upland rice varieties grown across Africa. We analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…The morning variable was statistically significant; those who participated in the auctions in the afternoons were more likely to upgrade to the alternative local rice varieties, which contrasts with previous findings in Benin, Senegal, and Uganda (Britwum et al, 2020; Demont et al, 2012, 2013b, 2013c). While further studies would be helpful in further explaining this phenomenon, time of auctions have on occasions not yielded any significant impacts on preferences and WTP (e.g., Demont et al, 2017; Diagne et al, 2017).…”
Section: Resultscontrasting
confidence: 90%
See 3 more Smart Citations
“…The morning variable was statistically significant; those who participated in the auctions in the afternoons were more likely to upgrade to the alternative local rice varieties, which contrasts with previous findings in Benin, Senegal, and Uganda (Britwum et al, 2020; Demont et al, 2012, 2013b, 2013c). While further studies would be helpful in further explaining this phenomenon, time of auctions have on occasions not yielded any significant impacts on preferences and WTP (e.g., Demont et al, 2017; Diagne et al, 2017).…”
Section: Resultscontrasting
confidence: 90%
“…As Tynan and Drayton (1987) noted, a number of reasons underscore consumer segmentation including geography and demographics. Although our segmentation is largely motivated by these two factors, this (Britwum et al, 2020;Dong et al, 2004;Newman et al, 2003).…”
Section: Results From the Double-hurdle Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Product profiles are defined as a trait package a new variety is expected to have to serve a specific market segment (meaning a group of users who are considered to have a relatively homogenous demand for a product or service). This paradigm shift in breeding strategies towards end-users is a necessary for step value chain development and Britwum et al [ 95 ] provide evidence that replacing a popular variety can only be done if a new product mimics key attributes of competing varieties, in addition to better performance on other attributes. However, our results showed that having the right product alone may not be sufficient to change farmer purchase decisions.…”
Section: Discussionmentioning
confidence: 99%